Seminar On The Use Of Social Media As Business Promotion In The Digital Economy Era For Students Of SMAN 5 Mataram As A Form Community Service - Syifa Ramadhani; Joni Rokhmat (Jurnal Pengabdian Pendidikan IPA Kontekstual, 2025)
The rapid development of the digital economy in Indonesia opens up great opportunities for the younger generation to develop businesses through social media. However, digital literacy and marketing skills among students still need to be improved. This article describes the implementation of the seminar "The Utilization of Social Media as Business Promotion in the Digital Economy Era" for students of SMAN 5 Mataram as a form of community service. The seminar, which was attended by 74 students from grades X to XII, presented two speakers with theoretical and practical backgrounds. This activity aims to improve students' knowledge and skills in using social media for business promotion. The results of observation and documentation show high student participation, positive responses, and increased understanding of digital marketing strategies. This activity makes an important contribution in increasing digital entrepreneurship literacy and student motivation to start using social media productively.